2017
DOI: 10.1159/000456030
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Mouse Cortex Postsynaptic Density following Neonatal Brain Hypoxia-Ischemia

Abstract: Proteomics of the synapses and postsynaptic densities (PSDs) have provided a deep understanding of protein composition and signal networks in the adult brain, which underlie neuronal plasticity and neurodegenerative or psychiatric disorders. However, there is a paucity of knowledge about the architecture and organization of PSDs in the immature brain, and how it is modified by brain injury in an early developing stage. Mass spectrometry (MS)-based proteomic analysis was performed on PSDs prepared from cortices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 82 publications
2
20
0
Order By: Relevance
“…Icam1 (intracellular adhesion molecule 1, expressed mainly by the endothelial cells forming the blood-brain barrier, involved in cell adhesion, leucocytes 20 and monocytes extravasation 21 , and morphogenesis) was up-regulated 1.6 fold in P17 jj rats (unpaired t-test with Welch correction, p < 0.0416). Similarly, we observed a Σ2.2 fold increase (unpaired t-test with Welch correction, p < 0.0315) of Chmp1a (charged multi-vesicular body protein 1a, regulating the neural progenitor cell proliferation 22 ). In adult jj Cll, Col4a3 (collagenase 4a3, the major structural component of the basal membrane, involved in the extracellular matrix remodeling 23 , providing the functional compartmentalization of the brain by clustering of growth factors, neurotransmitters/ions receptors, as well contributing to migration and differentiation 24 ), Casp6 (caspase 6 - proliferation and morphogenesis – Fig.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Icam1 (intracellular adhesion molecule 1, expressed mainly by the endothelial cells forming the blood-brain barrier, involved in cell adhesion, leucocytes 20 and monocytes extravasation 21 , and morphogenesis) was up-regulated 1.6 fold in P17 jj rats (unpaired t-test with Welch correction, p < 0.0416). Similarly, we observed a Σ2.2 fold increase (unpaired t-test with Welch correction, p < 0.0315) of Chmp1a (charged multi-vesicular body protein 1a, regulating the neural progenitor cell proliferation 22 ). In adult jj Cll, Col4a3 (collagenase 4a3, the major structural component of the basal membrane, involved in the extracellular matrix remodeling 23 , providing the functional compartmentalization of the brain by clustering of growth factors, neurotransmitters/ions receptors, as well contributing to migration and differentiation 24 ), Casp6 (caspase 6 - proliferation and morphogenesis – Fig.…”
Section: Resultssupporting
confidence: 64%
“…While we still have to confirm the role of the various genes identified in this study through methods such as gene silencing in vitro , our work suggests that the epigenetic impairment of neurodevelopmental processes in hyperbilirubinemia may be a relevant mechanism of bilirubin neurotoxicity. It is worth mentioning that Chmp1a, Arghap4 , Casp6, Ptk2, Col4a3 are genes involved in key steps of brain development as proliferation, migration, morphogenesis, neurite outgrowth and elongation, synaptogenesis, extracellular matrix formation and compartmentalization, as well the pathological axonal degeneration and apoptosis observed 19 , 22 , 25 , 41 , 42 in jj rats. By adding epigenetic dysregulation to the list of the mechanisms related to bilirubin-induced neuronal damage, we can confirm and expand the concept of a widespread toxic effect of the pigment on the CNS 43 , improving our understanding of the cellular and molecular mechanisms of bilirubin induced damage to CNS.…”
Section: Discussionmentioning
confidence: 99%
“…However, only limited information currently exists in support of PUR neuroprotection and its mechanisms, which may involve antiinflammatory, anti-apoptotic, and/or pro-angiogenic processes after ischemic insult (Chechneva et al, 2014;Chechneva and Deng, 2015). In addition, immediate microglial activation occurs following HI and mediates brain injury (Hagberg et al, 2015;Shao et al, 2017). Activated microglia mainly contributes to neuro-inflammation and releases inflammatory mediators including tumor necrosis factor-α and interleukin-1β, leading to neuronal dead and excitotoxic injury (Mallard et al, 2018).…”
Section: Neuronal Cell Death and Neuro-inflammation Were Attenuated Fmentioning
confidence: 99%
“…Synaptic proteins are directly involved in synaptic plasticity and related to cognitive function. A number of postsynaptic proteins including PSD95, PSD93, and synapse-associated protein 102 have been shown to be downregulated following early HI insult in neonatal mice (Shao et al, 2017). In addition, changes in synaptic morphology were associated with impaired recognition memory post-HI in neonatal rats (Ou-Yang et al, 2012).…”
Section: Pur Attenuated Synaptic Damage Following Hi Injurymentioning
confidence: 99%
“…Of special interest is the analysis of brain tissues, with diverse aims for the studies. For example, mice brains have been used to develop a stable isotope‐labeling kinetics‐multiple reaction monitoring (MRM) method to measure the clearance of proteins, to evaluate changes in the proteome after sensory deprivation of the primary somatosensory cortex, to study changes of the postsynaptic density following early brain hypoxia‐ischemia, and to monitor changes in the inferior colliculus after acute hydrogen sulfide exposure . In the last study, the authors identified 77 significantly altered proteins at any of the three time points spanned, some of them related with the metabotropic glutamate receptor group 1, and the inflammation mediated by chemokine and cytokine signaling pathways.…”
Section: Protein Expressionmentioning
confidence: 99%